An Alternative to Traditional Assessment: The Debate Showcase - Shrestha, Mona; Roffey, Christopher (Journal of Education and Research, 2018)
Recent debates indicate that there is a lack of focus on ontological transformation within university study due to an over-reliance on a tick-box approach to skill acquisition (Wilson et.al 2013, p. 1223). This paper discusses a recent initiative undertaken at a tertiary pathways institution focused on the utilisation of an alternative productive process to assess student learning. This alternative assessment approach was designed to better engage a specific student cohort that differs significantly from ‘conventional student bodies’ both socio-economically and educationally. It has been noted that many students within the cohort do not have the ‘assumed cultural capital’ (Delvin 2011) that facilitates success in a traditional tertiary environment. This paper focuses on how a debate assessment was modified using the concept of spiral curriculum (Bruner cited in Takaya 2008) to better align with the specific needs of the cohort and course outcomes. The concept was used as a scaffolding approach linked to real-life experience to help students make better sense of the key unit content. This paper argues that the showcase was generally successful, by shifting focus from a previously adversarial model to a reflective and ultimately transformative learning experience.